Comparing Narrative Microstructure between Bilingual Balochi-Persian and Monolingual Persian Preschoolers - Maryam Arabpour; Mahbube Nakhshab; Najme Abdolrashidi; Mahtab Molaiefard; Shima Bakhtyari; Hossein Ansari (Shiraz University of Medical Sciences, 2017)
Background: To date, with rapid increase of bilingual children, more attention about different patterns of the bilingual children narratives is needed. The aim of this study was to compare microstructure level of narratives generated by typical developing kindergarten children who were bilingual in Persian and Balochi with monolingual Persian speakers. Method: Thirty Persian-speaking monolingual and thirteen available bilingual children (aged 48 months old) participated in this study. Children's story telling was audio-recorded and analyzed using the Persian-NAP (Narrative Assessment Protocol) guidelines. Results: All of the NAP indicators include of group structure, phrase structure, modifiers, noun and verbs didn't show significant difference between monolingual and bilingual children (0.06≤p≤0.5). Conclusion: We didn't find different performance in the five NAP indicators between bilingual and monolingual children. It may be suggested that the different patterns of creating phrases and sentences in two languages don't affect the grammatical use of them in second language.